A high-value recycling method for lithium battery graphite negative electrode waste
Through high-temperature acid leaching, high-temperature calcination, wet material ball milling, spray drying and secondary calcining processes, spherical silicon carbon materials were prepared, solving the problem of low added value of recycled graphite in lithium-ion batteries, and achieving efficient resource regeneration and electrochemical performance improvement.
Patent Information
- Application Number
- CN202210485838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-05-06
AI Technical Summary
The added value of recycled graphite in existing lithium-ion batteries is low, making it difficult to meet the requirements of high-energy density negative electrode materials, and the recycling process consumes a lot of reagents and has low resource utilization efficiency.
The ball-type silicon carbon material products are prepared by high-temperature acid leaching, high-temperature calcining, wet material ball milling, spray drying and secondary calcining, which improves their electrochemical performance and realizes closed-circuit cycle of the process.
The high-value utilization of graphite anode materials for lithium-ion batteries has been achieved, the electrochemical performance of silicon-carbon materials has been improved, the reagent consumption has been reduced, and the process is environmentally friendly and sustainable.
Smart Images

Figure CN114843650B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field related to the treatment of solid waste in the battery industry, and in particular relates to a high-value recycling technology for waste graphite negative electrode materials of waste lithium batteries. Background Art
[0002] According to the latest data, by 2020, the average annual scrap volume of failed lithium batteries in my country exceeded 500,000 tons, causing serious environmental pollution and waste of resources. Among all the negative electrode materials for lithium batteries, graphite is the most commonly used. As the number of times lithium-ion batteries are charged and discharged increases, the interlayer spacing will expand or even peel off due to the embedding and extraction of lithium ions inside the graphite, causing the capacity of the battery material to gradually decay until it fails.
[0003] There are many ways to recycle waste lithium-ion negative electrode materials, among which the most important recycling method is to regenerate them into secondary electrode materials. However, due to its relatively low capacity (372 mAh / g), negative electrode graphite is difficult to meet the requirements of high energy density negative electrode materials, thus limiting its further development. However, silicon has a very high theoretical capacity (4200 mAh / g) and is regarded as a promising negative electrode material for the next generation. Therefore, considering mixing cheap recycled graphite with asphalt, nano-silicon powder and dispersant PVP to prepare silicon-carbon composite materials, its capacity can be greatly increased, thereby realizing the high-value utilization of graphite negative electrode waste.
[0004] The comparative patent (CN 111977646 A) firstly uses sulfuric acid to treat waste graphite for acid leaching to obtain purified graphite: the sulfuric acid concentration is 2 mol / L, the liquid-to-solid ratio is 50:3, the acid leaching time is 60 min, and the acid leaching temperature is 40°C; then the graphite is added to a mixed solution of an oxidant and an intercalating agent for reaction, and expandable graphite is obtained after filtration, water washing, and drying, and expanded graphite is obtained by calcining in a muffle furnace for a period of time: the oxidant is KMnO4 and the intercalating agent is concentrated nitric acid. The mass ratio of oxidant to graphite material is 1:2, the liquid-solid ratio of intercalant to graphite material is 15:1, the reaction time is 8 h, the subsequent calcination temperature is 900 °C, and the time is 30 s; finally, silicon-carbon material is added and ball milled to prepare expanded graphite / silicon-carbon composite material: among them, the mass ratio of expanded graphite to silicon-carbon material is 3:7, the ball milling speed is 450 r / min, the ball-to-material ratio in ball milling is 20:1, and the ball milling time is 7 h. The obtained expanded graphite / silicon-carbon composite material exhibits a discharge specific capacity of 1400 mAh / g at a rate of 0.1 C.
[0005] In view of the above-mentioned drawbacks of using waste graphite to prepare spherical silicon-carbon materials, which consumes a large amount of reagents and silicon-carbon materials. This invention intends to develop a new technology: that is, using high-temperature acid leaching, high-temperature calcination, wet material ball milling, spray drying and secondary calcination processes, that is, using wet ball milling, spray drying and high-temperature calcination processes to prepare spherical silicon-carbon material products with high sphericity and good uniformity, showing excellent electrochemical properties. In addition, ethanol and NMP in organic solvents can also be recycled, realizing a closed-loop cycle of the entire process. Summary of the invention
[0006] The purpose of the present invention is to address the problem of low added value of recycled graphite for lithium-ion batteries, and propose a high-temperature acid leaching, high-temperature calcination, wet material ball milling, spray drying and secondary calcination process to prepare spherical silicon-carbon material particles, and show excellent electrochemical properties, thereby realizing the resource regeneration and high-value utilization of lithium-ion batteries.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for recycling graphite negative electrode materials for lithium batteries, characterized in that it includes the steps of high-temperature acid leaching, high-temperature calcination, wet ball milling, spray drying and secondary calcination. The specific steps are as follows:
[0009] (1) The graphite negative electrode of the waste lithium-ion battery is leached with sulfuric acid. The leaching process requires stirring and water bath insulation treatment to obtain leached residue; then it is calcined at high temperature to obtain regenerated graphite.
[0010] (2) Add nano-silicon powder, PVP powder and alcohol solution to the regenerated graphite obtained in step (1), and perform a first ball milling in a ball mill to obtain a slurry.
[0011] (3) Adding asphalt / NMP solution to the mixed slurry obtained in step (2) for secondary ball milling to obtain secondary slurry.
[0012] (4) The secondary slurry obtained in step (3) is spray-dried to obtain a silicon-carbon material precursor.
[0013] (5) The precursor obtained in step (4) is subjected to secondary calcination to obtain a spherical silicon-carbon material product.
[0014] Furthermore, the reagent used in the acid leaching process of step (1) is sulfuric acid, the concentration is 50-500 g / L, the leaching temperature is 50-100°C, the liquid-solid ratio is 5:1-15:1, and the leaching time is 2-12 h; the temperature of the roasting process is 500-1500°C, and the holding time is 1-6 h. The roasting process requires the introduction of protective gas, which is N2 or Ar, with a flow rate of 60-120 mL / min.
[0015] Furthermore, the nano silicon powder in step (2) is 5% to 30% of the mass of graphite, and the PVP dispersant is 5% to 20% of the mass of silicon powder, and the liquid-solid ratio of alcohol to the overall material is 3:1 to 5:1. The ball milling speed is 200 to 500 rpm, and the ball milling time is 1 to 6 hours.
[0016] Furthermore, in step (3), the mass of asphalt added is 5-30% of the mass of graphite and silicon powder, and the liquid-solid ratio of NMP added to asphalt is 3:1-15:1. The ball milling speed is 200-500 rpm, and the ball milling time is 1-6 h.
[0017] Furthermore, in step (4), the inlet temperature of the spray drying equipment is 140-200°C, the outlet temperature is 60-100°C, the atomization pressure is 0.05-0.3 MPa, and the feed rate is 20-500 mL / min.
[0018] Furthermore, in step (5), the calcination temperature is 1000°C to 1600°C under normal pressure conditions, the calcination time is 1 to 8 h, the pressure is controlled at 1 atm, and a protective gas needs to be introduced during the calcination process. The protective gas is N2 or Ar, and the flow rate is 100 to 500 mL / min.
[0019] The key technical points of this invention are:
[0020] (1) This invention has the characteristic of low acid consumption. Specifically, compared with the reference document, the acid amount used in this invention is 0~4.0 mol / L, and the solid-liquid ratio is 1:0~15 g / L; while the acid concentration in the reference document is 0~5 mol / L, and the solid-liquid ratio is 1:0~100 g / L.
[0021] (2) The silicon-carbon material prepared by this invention has the characteristics of low silicon content and high electrochemical performance. Specifically, compared with the reference document, the silicon-carbon material synthesized in this application has a silicon content of 5% to 30% of the mass of graphite. More preferably, when the silicon content is 30%, the first capacity of the silicon-carbon material is 1136 mAh / g, the first efficiency is 88.2%, and the silicon capacity: silicon content = 3788:1; much higher than the first efficiency of 84.4% and the ratio of silicon capacity to content of 2328:1 in the reference document.
[0022] (3) The silicon-carbon material prepared by this invention is green and environmentally friendly. Specifically, compared with Reference Document 1, the alcohol and NMP used in this application are recovered by evaporation-condensation-fractionation. Moreover, the recovery rate of organic reagents is greater than 90%.
[0023] The technical solution disclosed in the reference document is: a method for preparing expanded graphite / silicon-carbon material using graphite negative electrode of waste batteries, characterized in that the method comprises:
[0024] After acid washing, filtering, washing and drying the graphite negative electrode sheet of the waste battery, the graphite carbon material detached from the negative electrode copper foil is obtained;
[0025] A mixed solution of concentrated sulfuric acid, potassium permanganate and hydrogen peroxide is added to the graphite carbon material to react, and then expanded graphite is obtained by washing, filtering and drying;
[0026] The expandable graphite is placed in a muffle furnace for calcination to obtain expanded graphite;
[0027] In the expanded graphite, the expanded graphite is mixed with a silicon-carbon material by ball milling to obtain an expanded graphite / silicon-carbon material;
[0028] After the expanded graphite is mixed by ball milling to obtain the expanded graphite / silicon-carbon material, the method further comprises: grinding the obtained expanded graphite / silicon-carbon material, and sieving the ground expanded graphite / silicon-carbon material powder to obtain recyclable expanded graphite / silicon-carbon material powder.
[0029] The technical solution of this application and the comparative documents have the following different technical features:
[0030] (1) The present application discloses a high-value recycling method for lithium battery graphite negative electrode waste, including high-temperature acid leaching, high-temperature calcination, wet material ball milling, spray drying and secondary calcination to prepare spherical silicon-carbon material particles;
[0031] The comparative document discloses a method for preparing expanded graphite / silicon-carbon material using graphite negative electrodes of waste batteries, including acid leaching, washing and drying the negative electrode copper foil of the lithium battery to obtain recycled graphite; adding a mixed solution of concentrated sulfuric acid, potassium permanganate and hydrogen peroxide to the recycled graphite, washing, drying and high-temperature calcining to obtain expanded graphite; adding silicon-carbon material to the expanded graphite and ball milling to obtain expanded graphite / silicon-carbon material powder.
[0032] It can be seen that the treatment process in the comparative document is different from that in the present application. It not only requires wet ball milling and spray drying technology that the present application does not have, but also the treatment method of the first calcined graphite powder in the middle is different from the treatment method of the graphite slag in the present application. The two target different objects, and the physicochemical properties of different targets are also different. Therefore, there is no technical basis for combining the subsequent treatment processes.
[0033] Specifically, the treatment method of adding concentrated sulfuric acid, potassium permanganate and hydrogen peroxide mixed solution to the graphite carbon powder in the comparative document is different from the sulfuric acid leaching and high-temperature roasting treatment method of the graphite slag in this application, and the concentrated sulfuric acid in the comparative document will have a negative impact on the subsequent drying and calcination of the graphite powder, easily generate sulfur dioxide toxic gas, and consume a large amount of reagents; while the method used in this application is different from that in the comparative document, pure graphite powder can be obtained by simple acid leaching and roasting, and the graphite powder obtained in the comparative document is not completely pure.
[0034] After the treatment of the present invention, the concentration of (Li, Al, Cu, Fe) ions in the graphite can be reduced to below 100 ppm, and the ash content (weight percentage) is less than 0.2%. In other words, the purity of the graphite is not less than 99.8%. The first capacity and first efficiency of the regenerated graphite at a rate of 0.1 C are 91.4% and 346.3 mAh / g, respectively, and the capacity retention rate after 100 cycles is 93.2%. Then, a spherical silicon-carbon material product is formed through wet ball milling, spray drying and high-temperature calcination processes, and the electrochemical performance of the silicon-carbon material is greatly improved. When the silicon content is 30%, the first capacity and first efficiency at a rate of 0.1 C are 1136 mAh / g and 88.4%, and the capacity retention rate after 100 cycles is 84.6%. In addition, in the process of preparing the silicon-carbon material, the solvents ethanol and NMP in the slurry can be continuously recycled, realizing a closed-loop cycle of the entire process. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 SEM images of spherical silicon carbon particles at different magnifications.
[0036] Figure 2 Cycling performance of spherical silicon-carbon materials. DETAILED DESCRIPTION
[0037] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.
[0038] The present invention provides a high-value recovery method for lithium battery graphite negative electrode waste, the process of the method mainly includes high-temperature acid leaching, high-temperature calcination, wet ball milling, spray drying and secondary calcination, etc., which are explained by specific embodiments below.
[0039] Example 1
[0040] (1) 20 g of negative electrode graphite (containing Li 1460 ppm, Cu 713 ppm, Fe 4592 ppm, Al 379 ppm, C97.9%) was leached with sulfuric acid: the sulfuric acid concentration was 200 g / L, the liquid-to-solid ratio was 10:1, the water bath temperature was 80 °C, and the leaching time was 4 h; then high-temperature calcination was carried out: the calcination temperature was 1000 °C, the holding time was 1 h, and the protective gas was N2 or Ar during the calcination process with a flow rate of 60 mL / min to obtain regenerated graphite (containing Li 34.8 ppm, Cu 164.4 ppm, Fe 35.4 ppm, Al 102.8 ppm, C 99.86%).
[0041] (2) The regenerated graphite obtained in step (1) is added with nano-silicon powder, dispersant PVP and alcohol for ball milling to form a slurry. The mass ratio of regenerated graphite: nano-silicon powder: PVP is 1:0.3:0.03, the liquid-solid ratio of alcohol to the overall material is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h.
[0042] (3) The slurry obtained in step (2) is added to the asphalt / NMP solution for secondary ball milling to form a secondary slurry, wherein the mass of asphalt is 10% of the sum of the masses of graphite and silicon powder, the liquid-solid ratio of NMP added to asphalt is 5:1, the secondary ball milling speed is 300 rpm, and the secondary ball milling time is 2 h.
[0043] (4) The secondary slurry obtained in step (3) is subjected to spray drying equipment for spray balling, wherein the inlet temperature is 160°C, the outlet temperature is 80°C, the physicochemical pressure is 0.1 Mpa, and the feed rate is 100 mL / min.
[0044] (5) The precursor material obtained in step (4) is subjected to secondary calcination to form a spherical silicon-carbon material product, wherein the inlet temperature is 1000 °C, the calcination time is 2 h, and a protective gas is introduced during the calcination process, with a N2 flow rate of 100 mL / min. The morphology of the silicon-carbon material product is as follows: Figure 1 The electrochemical performance is shown in Figure 2 The first capacity and first efficiency of the silicon-carbon material were 1136 mAh / g and 88.4%, and the capacity retention rate after 100 cycles was 84.6%.
[0045] Example 2
[0046] (1) 20 g of negative electrode graphite (containing Li 1168 ppm, Cu 666 ppm, Fe 4260 ppm, Al 308 ppm, C98.3%) was leached with sulfuric acid: the sulfuric acid concentration was 250 g / L, the liquid-to-solid ratio was 7.5:1, the water bath temperature was 90 °C, and the leaching time was 3 h; then high-temperature calcination was carried out: the calcination temperature was 1200 °C, the insulation time was 3 h, and the protective gas was N2 or Ar during the calcination process with a flow rate of 100 mL / min to obtain regenerated graphite (containing Li 15.2 ppm, Cu 112.6 ppm, Fe 21.6 ppm, Al 83.2 ppm, C 99.91%).
[0047] (2) The regenerated graphite obtained in step (1) is added with nano-silicon powder, dispersant PVP and alcohol for ball milling to form a slurry. The mass ratio of regenerated graphite: nano-silicon powder: PVP is 1:0.2:0.02, the liquid-solid ratio of alcohol to the overall material is 7.5:1, the ball milling speed is 400 rpm, and the ball milling time is 2 h.
[0048] (3) The slurry obtained in step (2) is added to the asphalt / NMP solution for secondary ball milling to form a secondary slurry, wherein the mass of asphalt is 15% of the sum of the masses of graphite and silicon powder, the liquid-solid ratio of NMP added to asphalt is 7.5:1, the secondary ball milling speed is 200 rpm, and the secondary ball milling time is 3 h.
[0049] (4) The secondary slurry obtained in step (3) is subjected to spray drying equipment for spray ball forming, wherein the inlet temperature is 180°C, the outlet temperature is 60°C, the physicochemical pressure is 0.2 Mpa, and the feed rate is 150 mL / min.
[0050] (5) The precursor material obtained in step (4) is subjected to secondary calcination to form a spherical silicon-carbon material product, wherein the inlet temperature is 1200°C and the calcination time is 3 h. During the calcination process, protective gas needs to be introduced, and the N2 flow rate is 200 mL / min.
[0051] Example 3
[0052] (1) 20 g of negative electrode graphite (containing Li 1650 ppm, Cu 682 ppm, Fe 5120 ppm, Al 408 ppm, C97.8%) was leached with sulfuric acid: the sulfuric acid concentration was 300 g / L, the liquid-to-solid ratio was 10:1, the water bath temperature was 90 °C, and the leaching time was 3 h; then high-temperature calcination was carried out: the calcination temperature was 1200 °C, the insulation time was 3 h, and the protective gas was N2 or Ar during the calcination process with a flow rate of 200 mL / min to obtain regenerated graphite (containing Li 2.1 ppm, Cu 82.3 ppm, Fe12.7 ppm, Al 67.5 ppm, C 99.94%).
[0053] (2) Add nano silicon powder, dispersant PVP and alcohol to the regenerated graphite obtained in step (1) and perform ball milling to form a slurry. The mass ratio of regenerated graphite: nano silicon powder: PVP is 1:0.1:0.01, the liquid-solid ratio of alcohol to the overall material is 10:1, the ball milling speed is 400 rpm, and the ball milling time is 2 h.
[0054] (3) Adding asphalt / NMP solution to the slurry obtained in step (2) for secondary ball milling to form a secondary slurry, wherein the mass of asphalt is 10% of the sum of the mass of graphite and silicon powder, the liquid-solid ratio of NMP to asphalt is 7.5:1, the secondary ball milling speed is 400 rpm, and the secondary ball milling time is 4 h.
[0055] (4) The secondary slurry obtained in step (3) is subjected to spray drying equipment for spray ball forming, wherein the inlet temperature is 200°C, the outlet temperature is 100°C, the physicochemical pressure is 0.3 Mpa, and the feed rate is 300 mL / min.
[0056] (5) The silicon-carbon material precursor obtained in step (4) is subjected to secondary calcination to form a spherical silicon-carbon material product, wherein the inlet temperature is 1500°C and the calcination time is 3 h. During the calcination process, protective gas needs to be introduced, and the N2 flow rate is 300 mL / min.
[0057] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for recovering high-value lithium battery graphite negative electrode waste, characterized in that: Lithium battery graphite negative electrode waste is subjected to sulfuric acid leaching to remove impurities in the waste, and then subjected to high-temperature calcination to remove organic matter and repair the internal structure; nano silicon powder, PVP powder, and alcohol solution are added to the regenerated graphite, and ball milling is first performed in a ball mill to obtain a slurry; then asphalt / NMP solution is added to the slurry and ball milling is performed for a second time to obtain a secondary slurry; the secondary slurry is then spray-dried to obtain a spherical silicon-carbon material precursor; in addition, alcohol / NMP gas is generated at the outlet during the spray drying process, and an organic solution is obtained by condensation, and pure alcohol and NMP reagents are subsequently recovered by fractionation; finally, the precursor is subjected to secondary high-temperature calcination to obtain a spherical silicon-carbon material product; The sulfuric acid concentration in the acid leaching process is 50~400 g / L, the leaching temperature is 50~100 ℃, the liquid-solid ratio is 5:1~15:1, and the leaching time is 2~12 h; the high-temperature calcination temperature of graphite is 500~1500 ℃, and the insulation time is 1~6 h; the calcination process requires the introduction of protective gas, which is N2 or Ar, with a flow rate of 60~120 mL / min.
2. A method for high-value recycling of lithium battery graphite negative electrode waste as claimed in claim 1, characterized in that: The mass ratio of graphite: nano-silicon powder: PVP is 1:0.05~0.4:0.005~0.04, the liquid-solid ratio of alcohol to the overall material is 2.5:1~7.5:1, the ball milling speed is 200~500 rpm, and the ball milling time is 1~6 h.
3. A method for high-value recycling of lithium battery graphite negative electrode waste as claimed in claim 1, characterized in that: The mass of asphalt added is 5-20% of the sum of the mass of graphite and silicon powder, the liquid-solid ratio of NMP added to asphalt is 3:1-15:1, the secondary ball milling speed is 200-500 rpm, and the secondary ball milling time is 1-6 h.
4. A method for high-value recycling of lithium battery graphite negative electrode waste as claimed in claim 1, characterized in that: The inlet temperature of the spray drying process equipment is 120~200 ℃, the outlet temperature is 60~100 ℃, the atomization pressure is 0.05~0.3 MPa, and the feed rate is 20~500 mL / min.
5. A method for recycling lithium battery graphite negative electrode waste in high value according to claim 1, characterized in that: The secondary calcination temperature is 1000 ℃~1600 ℃, the calcination time is 1~8 h, and a protective gas needs to be introduced during the calcination process. The protective gas is N2 or Ar, and the flow rate is 100~500 mL / min.
Citation Information
Patent Citations
Method for preparing expanded graphite / silicon carbon material from graphite negative electrode of waste battery
CN111977646A
Lithium ion battery silicon-carbon composite negative pole material and preparation method thereof
CN106299277A
Preparation method of silicon-carbon negative electrode material for high-compaction-density lithium ion battery
CN108736007A
Method for preparing silicon-carbon negative electrode material by using waste graphite of lithium ion battery
CN114335495A